2005
DOI: 10.2106/jbjs.d.01796
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality After Hip Fracture

Abstract: The thirty-day mortality following surgery for a hip fracture was 9%. Patients with medical comorbidities that delayed surgery had 2.5 times the risk of death within thirty days after the surgery compared with patients without comorbidities that delayed surgery. Mortality was not increased when the surgery was delayed up to four days for patients who were otherwise fit for hip fracture surgery. However, a delay of more than four days significantly increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(167 citation statements)
references
References 7 publications
9
154
0
4
Order By: Relevance
“…44 Delayed time to surgical fixation for hip fractures increases morbidity and mortality and decreases future function. 15,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]46 Our study confirmed this. Increasing time to surgery led to an increasing number of complications (P ¼ .0492) and a trend toward higher mortality (P ¼ .091).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…44 Delayed time to surgical fixation for hip fractures increases morbidity and mortality and decreases future function. 15,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]46 Our study confirmed this. Increasing time to surgery led to an increasing number of complications (P ¼ .0492) and a trend toward higher mortality (P ¼ .091).…”
Section: Discussionsupporting
confidence: 87%
“…[25][26][27] Many authors have therefore focused on factors that may decrease complications and improve mortality following hip fracture surgery. [15][16][17][18][19] Time to surgery, in particular, has attracted considerable attention. Zuckerman et al found that an operative delay of more than 2 calendar days doubled the 1-year mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractures of the hip and vertebral body are the most commonly associated injuries with increased post-injury mortality. [9][10][11][12][13][14][15] Mortality after vertebral fractures has been reported to range between 16% and 60% greater than an unaffected population. [15][16][17] In a previous publication, these two morbidity scores provided a control for the medical comorbidities of patients with osteoporosis who sustained vertebral compression fractures treated either surgically or conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 60% of women and 30% of men at the age of 60 or above suffer from osteoporosis. Twelve months after a hip fracture, there is a 24% mortality rate (Giversen, 2007;Jiang et al, 2005;Moran, Wenn, Sikand, & Taylor, 2005;Rosell & Parker, 2003); 26% of those with a hip fracture remain in nursing homes (Rosell & Parker, 2003;Wehren & Magaziner, 2003) and the remaining 50% never regain independent living (Sernbo & Johnell, 1993;Wehren & Magaziner, 2003). In Australia, one in three men and one in two women are at risk of osteoporosis.…”
Section: Bone Anatomy and Osteoporosismentioning
confidence: 99%